1998
DOI: 10.1111/j.1349-7006.1998.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of N‐Nitroso‐N‐methylurea‐induced Rat Mammary Carcinogenesis by Soy Foods or Biochanin A

Abstract: We examined the effects of soybeans, a soy product (miso) and biochanin A, an isoflavone derivative, on N-nitroso-N-methylurea (MNU)-induced rat mammary carcinogenesis. Seven-week-old female CD/Crj rats received a single i.v. dose (40 mg/kg body weight) of MNU. After administration of MNU, rats were fed diet containing 0% (control), 2% or 10% soybeans, or 10% miso as a soy-supplemented diet, or 10 or 50 mg/kg biochanin A. All rats were observed for 18 weeks after MNU administration. At 18 weeks, the multiplici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 20 publications
0
47
1
2
Order By: Relevance
“…They have also been suggested as novel candidate drugs for AD [29]. As one of the phytoestrogen compounds, biochanin A, has been shown to have an important effect in cancer protection [21,22]. However, there is still much to learn about this phytoestrogen and its beneficial effects on human health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also been suggested as novel candidate drugs for AD [29]. As one of the phytoestrogen compounds, biochanin A, has been shown to have an important effect in cancer protection [21,22]. However, there is still much to learn about this phytoestrogen and its beneficial effects on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Its chemical structure resembles that of endogenous estrogen, which is able to displays agonistic and antagonistic interactions with the estrogen receptor. Over the past few years, biochanin A has been applied in research on cancer prophylaxis and neuroprotection studies [20][21][22][23]. Despite the many considerable efforts to study the beneficial effects of biochanin A, there remains a significant lack of understanding of the effects of this compound on the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Constantinou et al (2001) found that an exposure to SPI that was depleted of IFs had the most significant effect on tumour latency and multiplicity. Also, an exposure to 10% miso Early life genistein exposures in modifying breast cancer risk A Warri et al was reported to reduce mammary tumorigenesis in rats (Gotoh et al, 1998). To summarise, genistein/SPI exposure limited to the prepubertal period appears to reduce later mammary cancer risk in rats, but the effect is mostly lost if the exposure remains high throughout adult life.…”
Section: Ratsmentioning
confidence: 99%
“…Each of the four studies that used non-fermented, whole soyabean products reported protective effects (Troll et al 1980;Gridley et al 1983;Barnes et al 1990;Gotoh et al 1998b). In the study by Troll et al (1980), however, raw soyabeans were used and the body weight of soyabean-fed rats was 10 % lower than that of control animals.…”
Section: Soyabean Intake and Breast Cancermentioning
confidence: 99%